Canonical Metrics on Twisted Quiver Bundles over a Class of Non-Compact Gauduchon Manifold - Shi-Fan Cai; Sudhakar Kumar Chaubey; Xin Xu; Pan Zhang; Zhi-Heng Zhang (Axioms, 2024)
The aim of this paper is to prove a theorem for holomorphic twisted quiver bundles over a special non-compact Gauduchon manifold, connecting the existence of <semantics>(σ,τ)</semantics>-Hermite–Yang–Mills metric in differential geometry and the analytic <semantics>(σ,τ)</semantics>-stability in algebraic geometry. The proof of the theorem relies on the flow method and the Uhlenbeck–Yau’s continuity method.